A new species of Gamasiphis Berlese (Acari: Ologamasidae) from Russia (Sakhalin and Kuril Islands) with a key to the Asian species - Marchenko, Irina I. (Zootaxa, 2013)
Gamasiphis ochotensis sp. n. is described based on the morphology of females and males collected from litter and soil in the Sakhalin and Kuril Islands of Far East Russia. A key for the separation of females of 10 recognisable species of Gamasiphis distributed in Asia is provided.